Halal Tourism Development at Santen Sharia Beach, Banyuwangi: Opportunities, Challenges, and Sustainable Integration with Local Islamic Traditions - Endang Mintarja; Ali Masykur; Oneng Nurul Bariyah (Universitas Negeri Jakarta, 2026)
Halal tourism has emerged as a global competitiveness strategy, yet its implementation often faces a misalignment between global standards and local socio-cultural realities. This study analyzes the development of halal tourism at Santen Sharia Beach, Banyuwangi, through a qualitative approach. By integrating SWOT analysis with socio cultural and sustainability perspectives, we identify that the destination’s development is characterized by a